2016
DOI: 10.1007/s13300-016-0198-3
|View full text |Cite
|
Sign up to set email alerts
|

Incretin-Based Therapy and Risk of Pancreatic Cancer in Patients with Type 2 Diabetes Mellitus: A Meta-analysis of Randomized Controlled Trials

Abstract: IntroductionThe present study aims to evaluate the risk of pancreatic cancer with incretin-based therapy among patients with type 2 diabetes mellitus (T2DM).MethodsWe searched EMBASE, MEDLINE, the Cochrane Central Register of Controlled Trials and ClinicalTrials.gov for eligible studies published up to March 06 2016. This meta-analysis includes all studies reporting adverse events of pancreatic cancer with use of incretin-based therapies compared with placebo or non-incretin anti-diabetic drugs in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 63 publications
(70 reference statements)
4
18
0
Order By: Relevance
“…For pancreatic cancer, our findings are qualitatively consistent with results reported by Romley et al, Gokhale et al, Azoulay et al, Dore et al and Funch et al as well as a recent meta‐analysis of 24 clinical trial studies. However, the results differ from those reported by Elashoff et al, Boniol et al and Tseng .…”
Section: Discussionsupporting
confidence: 92%
“…For pancreatic cancer, our findings are qualitatively consistent with results reported by Romley et al, Gokhale et al, Azoulay et al, Dore et al and Funch et al as well as a recent meta‐analysis of 24 clinical trial studies. However, the results differ from those reported by Elashoff et al, Boniol et al and Tseng .…”
Section: Discussionsupporting
confidence: 92%
“…In 2014, a joint study was published in the New England Journal of Medicine , stating that the agencies had not yet reached a final conclusion regarding a possible relationship . Since then, several literature reviews have been conducted regarding incretin‐based drugs and pancreatic cancer …”
Section: Introductionmentioning
confidence: 99%
“…Although a number of cohort studies and meta‐analyses reported no association between incretin‐based therapies and risk of acute pancreatitis and pancreatic cancer , other studies have reported an increased risk of acute pancreatitis with such agents . In a meta‐analysis based on pooled data from the SAVOR‐TIMI 53, EXAMINE and TECOS trials, Tkáč and Raz reported a significant increase in the incidence of acute pancreatitis [odds ratio (OR): 1.79; 95% confidence intervals (CI) 1.13, 2.82] in people treated with DPP‐4i when compared with placebo.…”
Section: Introductionmentioning
confidence: 99%